Efeitos da Seleção para Peso Pós-desmame sobre Medidas Corporais e Perímetro Escrotal de Machos Nelore de Sertãozinho (SP) - Cyrillo, Joslaine Noely Dos Santos Goncalves; Razook, Alexander George; De Figueiredo, Leopoldo Andrade; Neto, Luiz Martins Bonilha; Ruggieri, Ana Cláudia; Tonhati, Humberto [UNESP] (FapUNIFESP (SciELO), 2000)
The objective of this study was to evaluate the indirect effects of selection for post-weaning weight on body measures and scrotal perimeter of 809 Nellore males from selected herds (NeS and NeT) and control herd (NeC), of the Estação Experimental de Zootecnia de Sertãozinho. The statistical analyses were performed by using a sire mixed model where the random source of variation, sires, was nested within herds. The fixed effects were herds, year of performance test (PGP), age of cow and age of the animal as a covariate. The average genetic change for final weight, corrected for 378 days of age (W378), calculated as a deviation from the NeC herd, were 40.2 and 44.3 kg for the NeS and NeT herds, respectively. The correlated changes, for the other traits were, in the same order, 4.5 and 4.5 cm for hip height (HH); 6.2 and 7.0 cm for chest girth (CG); 5.8 and 6.3cm for body length (BL); 2.9 and 2.0 cm for dorsal line length (DL); 1.7 and 2.4 cm for rump length (RL); 1.0 and 1.3 cm for distance between pin bones (DPB); 1.8 and 2.6 cm for distance between hip bones (DHP); and 1.3 and 2.2 cm for scrotal perimeter (SP). The results of this study showed that the direct selection for postweaning weight promoted correlated positive responses in the body dimensions and also in the scrotal perimeter of Nellore males.
Effects of Post-Weaning Weight Selection on Body Measurements and Scrotal Perimeter in Nellore Males of Sertãozinho (SP)
Keywords: Body measurements; Scrotal perimeter; Selection; Weaning weight; Animalia; Nes